Deciphering the design of the tropomyosin molecule - Brown, Jerry H. (The National Academy of Sciences, 2001)
The crystal structure at 2.0-Å resolution of an 81-residue N-terminal fragment of muscle α-tropomyosin reveals a parallel two-stranded α-helical coiled-coil structure with a remarkable core. The high alanine content of the molecule is clustered into short regions where the local 2-fold symmetry is broken by a small (≈1.2-Å) axial staggering of the helices. The joining of these regions with neighboring segments, where the helices are in axial register, gives rise to specific bends in the molecular axis. We observe such bends to be widely distributed in two-stranded α-helical coiled-coil proteins. This asymmetric design in a dimer of identical (or highly similar) sequences allows the tropomyosin molecule to adopt multiple bent conformations. The seven alanine clusters in the core of the complete molecule (which spans seven monomers of the actin helix) promote the semiflexible winding of the tropomyosin filament necessary for its regulatory role in muscle contraction.